Pengaruh Substitusi Wortel Parut Terhadap Sifat Sensori Dan Kesukaan Muffin (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of grated carrot addition on muffin quality, including aspects of shape, color, aroma, texture, and taste. Muffins are a popular bakery product due to their soft texture and varied flavors, which can be enhanced by the addition of nutritious ingredients such as carrots. Carrots are rich in vitamin A, fiber, and beta-carotene which can improve the nutritional value as well as the sensory characteristics of muffins. This study used an experimental method with a completely randomized design (CRD) and four treatments (0%, 10%, 20%, and 30% grated carrot substitution) with three replications. Sensory quality tests and hedonic tests were conducted with untrained panelists, and data were analyzed using one-way ANOVA. The results showed that muffins with 20% grated carrot substitution had the best scores in terms of shape and aroma, while 30% substitution produced the best color, texture, and taste in the sensory quality test. The hedonic test showed that 20% substitution was most preferred for shape and color, while 30% substitution was preferred for aroma, texture, and taste. Furthermore, the addition of grated carrots to muffins not only improves the organoleptic quality but also provides additional beneficial nutritional content, such as vitamin A and fiber. This study concluded that the addition of grated carrots can improve the overall quality of muffins and recommends using a 30% substitution for optimal results, as it can enhance the aroma, taste, and texture that consumers prefer without reducing the overall quality of the muffins.